Cytoplasmic p21WAF1/CIP1 expression is correlated with HER-2/ neu in breast cancer and is an independent predictor of prognosis. - Winters, Z; Leek, R; Bradburn, M; Norbury, C; Harris, A (2003)
BACKGROUND: HER-2 (c-erbB2/Neu) predicts the prognosis of and may influence treatment responses in breast cancer. HER-2 activity induces the cytoplasmic location of p21WAFI/CIPI in cell culture, accompanied by resistance to apoptosis. p21WAFI/CIPI is a cyclin-dependent kinase inhibitor activated by p53 to produce cell cycle arrest in association with nuclear localisation of p21WAFI/CIPI. We previously showed that higher levels of cytoplasmic p21WAFI/CIPI in breast cancers predicted reduced survival at 5 years. The present study examined HER-2 and p21WAFI/CIPI expression in a series of breast cancers with up to 9 years of follow-up, to evaluate whether in vitro findings were related to clinical data and the effect on outcome. METHODS: The CB11 anti-HER2 monoclonal antibody and the DAKO Envision Plus system were used to evaluate HER-2 expression in 73 patients. p21WAFI/CIPI staining was performed as described previously using the mouse monoclonal antibody Ab-1 (Calbiochem, Cambridge, MA, USA). RESULTS: HER-2 was evaluable in 67 patients and was expressed in 19% of cases, predicting reduced overall survival (P = 0.02) and reduced relapse-free survival (P = 0.004; Cox regression model). HER-2-positive tumours showed proportionately higher cytoplasmic p21WAFI/CIPI staining using an intensity distribution score (median, 95) compared with HER-2-negative cancers (median, 47) (P = 0.005). There was a much weaker association between nuclear p21WAFI/CIPI and HER-2 expression (P = 0.05), suggesting an inverse relationship between nuclear p21WAF1/CIP1 and HER-2. CONCLUSION: This study highlights a new pathway by which HER-2 may modify cancer behaviour. HER-2 as a predictor of poor prognosis may partly relate to its ability to influence the relocalisation of p21WAFI/CIPI from the nucleus to the cytoplasm, resulting in a loss of p21WAFI/CIPItumour suppressor functions. Cytoplasmic p21WAFI/CIPI may be a surrogate marker of functional HER-2 in vivo.